What motivates Malaysian working adults to watch broadcast television? - Pajen Singh, Daljit Kaur (2000)
The objective of the study is to understand and develop a conceptual framework to evaluate the behaviour that motivates broadcast television viewing among Malaysian working adults. Working adults were chosen as the focus group of this study since they're away from home most of the time due to their work demands. The little time left after work or during weekends would mean a lot to this group. Unlike in the West, the need for such research arises since there are very limited studies conducted in this area in Malaysia. It is proven, as the literatures were mostly sourced from western researchers. The study utilized 154 respondents comprising of working adults, from Subang Hi-Tech Park, Shah Alam. In collecting the data, the respondents were questioned regarding their viewing motivations, viewing behaviour, television exposure and affinity as well as demographics. Three hypotheses were tested, of which the first is " There was a relationship between working adults demographics with television exposure and affinity". The second hypothesis, " There was a relationship between working adults demographic and television viewing motivations" and the third hypothesis which is " There was a relationship between working adults demographics and viewing behaviour". The respondents consisted 75% (115) of whom are married and remainder 25% (39) as being single. Almost all of the respondents i.e. 89% (137) have working experience of more than 4 years. Majorities (64%) of the respondents are between the age of 31 to 40 years and are working in the middle management level (64%). 31% are with Postgraduate Degree, 29% with Certificate and 24% with professional qualification. The findings suggest that the most important reason for adults viewing motivation is for seeking informative programs. Consistent with previous research by Rubin A.M.(1986), the number of hours spent yesterday and hours per day on average spent to watch broadcast television on a weekday, are important measures for the purpose of viewing exposure and affinity. The most important behaviour is the act of channel switching until something interesting is found for viewing. With this study, media related agencies would be able to have an insight on Malaysian working adult audiences viewing behaviour towards broadcast television. The author hopes that programmes offered in the future by television channels would take into consideration the needs of this niche group.